Correlation of radiological and histopathological findings in the diagnosis of benign bone tumors - Eriten, Berna; Menekşe, Serdar (The European Research Journal, 2025)
Objectives: Diagnosis of benign bone tumors is one of the diagnostic questions in the clinical practice which has an impact on the patient's quality of life. The work aimed to define the radiographic and histologic complementary diagnosis for benign bone tumors. Methods: The present cross-sectional study included one hundred and forty-two patients with benign bone and soft tissue tumors referred to and followed up in the Adana Seyhan Hospital over a study period of 2010 to 2023. Patients were categorized based on the tumor type and radiological imaging was done through X-ray, Computed Tomography (CT), and Magnetic Resonance Imaging (MRI) scans. These results were then compared to histopathologic outcomes. Diagnostic indices such as the percentage accuracy, sensitivity, specificity, and positive and negative predictive values were estimated. Results: In the study, 43.7% of the tumors were cartilaginous. MRI had the highest diagnostic accuracy (sensitivity of 96.9%, specificity of 83.3%, P